2011
DOI: 10.1017/s0033291711001139
|View full text |Cite
|
Sign up to set email alerts
|

Drug cue induced overshadowing: selective disruption of natural reward processing by cigarette cues amongst abstinent but not satiated smokers

Abstract: These findings provide the first evidence that drug cues interact with reward processing in a drug dependent population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 49 publications
3
30
0
Order By: Relevance
“…More generally, on-line iterative reinforcement learning in which behaviour (and hence sampling of the environment) changes after every experience often does not have the kind of optimality guarantees that off-line learning has (Bertsekas and Tsitsiklis, 1996), and may lead to self-reinforcing loops of choice and reward (Hogarth et al, 2007). One such effect was shown directly by Freeman et al (2012), who have found that abstinent smokers were more likely to associate a drug cue with reward than a non-drug cue. Indeed, attentional mechanisms are clearly important in learning (Pearce, 1997;Dayan et al, 2000) and possibly in the maintenance of addiction (Hogarth and Chase, 2011;Hogarth et al, 2013;Wiers et al, 2011).…”
Section: Individual Variability In Addiction Vulnerabilitymentioning
confidence: 99%
“…More generally, on-line iterative reinforcement learning in which behaviour (and hence sampling of the environment) changes after every experience often does not have the kind of optimality guarantees that off-line learning has (Bertsekas and Tsitsiklis, 1996), and may lead to self-reinforcing loops of choice and reward (Hogarth et al, 2007). One such effect was shown directly by Freeman et al (2012), who have found that abstinent smokers were more likely to associate a drug cue with reward than a non-drug cue. Indeed, attentional mechanisms are clearly important in learning (Pearce, 1997;Dayan et al, 2000) and possibly in the maintenance of addiction (Hogarth and Chase, 2011;Hogarth et al, 2013;Wiers et al, 2011).…”
Section: Individual Variability In Addiction Vulnerabilitymentioning
confidence: 99%
“…This excessive effect of smoking cues on neural activation was shown to be modulated by genes related to the dopamine transporter [89] and to be reduced by administration of varenicline, a smoking cessation medication that functions as a partial agonist of nicotinic receptors [90]. An attentional bias toward smoking cues was also identified in abstinent smokers, which was related to activation in DLPFC, putamen, posterior cingulate cortex and primary motor cortex [91] and was shown to overshadow the value of neutral cues predicting natural reward [92]. Finally, the neural response to smoking cues compared to the neural activation to pleasant stimuli was shown to be predictive of abstinence [93].…”
Section: Findings In Human Smokersmentioning
confidence: 99%
“…An attentional bias toward smoking cues was also identified in abstinent smokers, which was related to activation in DLPFC, putamen, posterior cingulate cortex and primary motor cortex [91] and was shown to overshadow the value of neutral cues predicting natural reward [92]. Finally, the neural response to smoking cues compared to the neural activation to pleasant stimuli was shown to be predictive of abstinence [93]. …”
Section: Findings In Human Smokersmentioning
confidence: 99%
“…Abstinent smokers demonstrate increased desire to smoke (i.e. craving) (Shiffman and Jarvik 1976), along with diminished interested in pleasant events, evidenced by decreased attentional bias toward positive stimuli (Dawkins et al 2006; Freeman et al 2012; Leventhal et al 2012; Powell et al 2002b; Powell et al 2004); lower ratings of attractiveness for unfamiliar faces (Attwood et al 2009); lower ratings of anticipated enjoyment in activities; and reduced responsiveness to monetary reward (Dawkins et al 2006; Geier et al 2014; Powell et al 2002a; Powell et al 2004). Consistent with behavioral evidence, we recently demonstrated that 24 hr abstinence from smoking—compared with smoking as usual—was associated with both heightened response to smoking reward (i.e., puffs of a cigarette delivered after the scan) and attenuated response to monetary reward within the ventral striatum (Sweitzer et al 2013b)—a key component of reward circuitry thought to encode motivational salience of primary and secondary reinforcers (Bassareo and Di Chiara 1999; Delgado et al 2000; O’Doherty 2004; Schultz 2000).…”
Section: Introductionmentioning
confidence: 99%